KEMANDIRIAN BELAJAR DAN DUKUNGAN KELUARGA TERHADAP KEMATANGAN KARIER PADA SISWA SMA - Nindya Arum Rachmasari; Lucky Purwantini (Jurnal Selaras : Kajian Bimbingan dan Konseling serta Psikologi Pendidikan, 2018)
ABSTRACT This study aims to examine self regulated learning and family support for career maturity. Subjects were 42 students of class XII in SMAN Y Karawang. This study used self regulated learning scale with Cronbach alpha 0,861, family support scale with Cronbach alpha 0,876, and career maturity scale with Cronbach alpha 0,931. Data analysis using multiple regression. This study found that there was an influence between self regulated learning and family support to career maturity. Keywords: career maturity, family support, self regulated learning